Wet Strength and Antibacterial Performance of Cellulosic Paper Induced by Maleic Anhydride-Acylated Chitosan - Zicheng Chen (BioResources, 2014)
Paper sheets were dipped in maleic anhydride-acylated chitosan (MAAC) to enhance their wet strength and antibacterial performance. The wet strength of paper sheets treated with MAAC or chitosan solutions and cured at 90 and 170 °C was investigated. Escherichia coli was used to evaluate the antibacterial performance of the treated paper sheets. The antibacterial performance was determined by measuring the absorbance at 610 nm based on the turbidity of the bacterial suspension on the surface of the treated paper sheets. The MAAC performed better than chitosan in improving wet strength, especially in the case of permanent wet strength. Paper sheets treated with MAAC under certain conditions resulted in 23 to 33% improvements in the permanent wet strength. As a result of the surface treatment, a reduction of at least 80% in E. coli growth was observed. The MAAC was more efficient in inhibiting the growth of E. coli than chitosan.